Differences in Students' Truancy in Terms of Gender and Age - Nurawinata, Harry; Wibowo, Mungin Eddy; Awalya, Awalya (Jurnal Bimbingan Konseling, 2022)
Truancy is a situation in which students violate the rules and regulations at school. Based on this background, the present study investigated 3 vocational schools in Rembang Regency. It aimed at determining differences in truancy in terms of gender, determining truancy in terms of age, and determining school, personal and family factors underlying this violation. To do so, the cross-sectional design was employed. The cluster technique divided the population into sub groups, where the sub groups consisting of the same elements in 248 samples. Following the grouping, the samples data were collected using a truancy scale. Then, the Microsoft excel software was used to generate the respondents’ characteristics. Based on the chi square test, there were differences in truancy between gender and age.